2015
DOI: 10.1074/jbc.m114.585703
|View full text |Cite
|
Sign up to set email alerts
|

Acceleration of α-Synuclein Aggregation by Exosomes

Abstract: Background: Cell-to-cell transmission of α-syn via exosomes has been proposed to propagate Parkinson disease pathology.Results: Exosomes contain gangliosides, several other lipid classes, and proteins. Exosomes and ganglioside vesicles accelerate α-syn aggregation. Vesicles made of other membrane lipids do not.Conclusion: Exosomes provide catalytic environments for nucleation of α-syn aggregation.Significance: Revealing factors that promote α-syn aggregation may provide insight into Parkinson disease pathogene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
276
0
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 322 publications
(295 citation statements)
references
References 86 publications
15
276
0
4
Order By: Relevance
“…Human α-synuclein, which was used for the QCM-D measurements, was expressed in E. coli from the aS-pT7-7 plasmid (kindly provided by H. Lashuel) and purified using heat treatment, ion exchange, and gel filtration chromatography as previously described. 48 For perdeuteration of α-synuclein, the resistance marker of aS-pT7-7 was changed by in vitro transposition from ampicillin to kanamycin using the (EZ-Tn5) <KAN-2> Insertion Kit from Epicenter Biotechnologies. The modified plasmid was then transformed into BL21(DE3) cells.…”
Section: ■ Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Human α-synuclein, which was used for the QCM-D measurements, was expressed in E. coli from the aS-pT7-7 plasmid (kindly provided by H. Lashuel) and purified using heat treatment, ion exchange, and gel filtration chromatography as previously described. 48 For perdeuteration of α-synuclein, the resistance marker of aS-pT7-7 was changed by in vitro transposition from ampicillin to kanamycin using the (EZ-Tn5) <KAN-2> Insertion Kit from Epicenter Biotechnologies. The modified plasmid was then transformed into BL21(DE3) cells.…”
Section: ■ Methodsmentioning
confidence: 99%
“…66 α-Synuclein expression was induced with 0.2 mM isopropyl thiogalactopyranoside and the deuterated protein purified as described previously. 48 The molecular mass for d-α-synuclein was determined by mass spectrometry to be 15209 Da in H 2 O. If all labile deuterons in α-synuclein are assumed to be exchanged, the extent of deuteration is calculated to be 97%.…”
Section: ■ Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, it has been demonstrated that the exosomes abbreviate the time of aggregation for this protein, which suggests that they provide the catalytic environments for α-synuclein nucleation. Interestingly, vesicles isolated from extracted exosome lipids were indeed able to accelerate this aggregation process, suggesting that the lipids in exosomes were sufficient for the observed catalytic effect (Grey et al 2015). In particular, the acceleration of α-synuclein aggregation as observed in the presence of exosomes was reproduced by vesicle preparations composed of fluid lipid bilayers that contain gangliosides, a type of lipid that is highly enriched in rafts (Pike 2003).…”
Section: Exosomes a Bubble Ride For Synucleinmentioning
confidence: 99%
“…L'équilibre entre ces deux formes joue un rôle pour la fonction d'-syn [3]. De plus, la protéine interagit avec un grand nombre de surfaces in vitro, par exemple des nanoparticules, surfactants et bicouches lipidiques (vésicules), et son interaction avec ces surfaces peut moduler la cinétique de formation de fibres amyloïdes par -syn [4,5]. Enfin, il a été récemment montré qu'-syn peut former des fibres incorporant des lipides [6].…”
Section: Données De L'european Parkinson Disease Associationunclassified